EYEBALL SAVING ON UNILATERAL OCULAR TRAUMA AFTER MOTOR VEHICLE ACCIDENT: AN EMERGENCY ROOM CASE REPORT: Poster Presentation - Case Report - General practitioner - Fatina Qonita; Umi Yuliani (Majalah Oftalmologi Indonesia, 2023)
Introduction : One of the main causes of reduced or lost vision is ocular trauma. The second common cause of ocular trauma, particularly among younger people, was motor vehicle accidents (MVA). Case Illustration : A 16-year-old female with a history of MVA was brought to the emergency room. She complained of pain with her left eye. Visual acuity was no light perception. Linear wound was found from limbus to limbus and 0.5cm beyond the limbus to medial. The lens cannot be assessed because of the prolapse of the iris and choroid, abnormal corneal and iris structures, and active hemorrhage. CT Scan showed collapsed and deformed on the left bulbi. Discussion : In this case, initial surgery was performed by exploration and reposition of the eyeball then close the wound through primary hecting on the cornea. Following surgery, 8 days later, patient went for an eye ultrasonography checked and showed that the left globe was ruptured, along with a subcutaneous hematoma and emphysema. Even though, patient’s visual acuity improved into the stage of light perception. The left eye's follow-up examination revealed hyperemic conjunctiva, a hazy cornea with a horizontal scar-forming, and securely closed sutures. Iris seems superior, however, it was impossible to see the pupil. Conclusion : Ocular trauma causes tremendous morbidity as well as psychological and social distress, and an economic burden. Thus, proper diagnosis and therapy are related to the prognosis of visual acuity, eye anatomy, and future complications.